HUMAN TENOCYTES ARE STIMULATED TO PROLIFERATE BY ACETYLCHOLINE THROUGH AN EGFR SIGNALLING PATHWAY. Issue 9 (10th May 2013) - Fong, G; Backman, L J; Andersson, G; Scott, A; Danielson, P
Abstract : Introduction: Studies on human patellar and Achilles tendons have shown that tendon cells not only have the capacity to produce acetylcholine (ACh) but also express muscarinic ACh receptors (mAChRs), of subtype M2 (M2 R), and that both the production and receptor expression seem to be increased in tendinosis. Hypercellularity and angiogenesis are key histopathologic features in tendinosis tissue. In this study, we aimed at testing the hypothesis that ACh increases the proliferation rate of tenocytes through mAChR stimulation, as well as investigating whether this mechanism is mediated by the extracellular activation (phosphorylation) of the epidermal growth factor receptor (EGFR), which has been shown to elicit DNA synthesis and cell proliferation in other fibroblastic cells types, through an intracellular pathway including activation/phosphorylation of the mitogen activated protein kinases ERK1/2. Methods: Human Achilles tenocytes were seeded in cell culture plates and incubated in serum-starved conditions. The cells were pre-treated with the EGFR inhibitor AG1478, the matrix metalloproteinase (MMP) inhibitor GM6001 or the mAChR antagonist atropine. The cells were then stimulated with ACh (10 −6  M) or the vehicle. To determine the levels of phospho-ERK1/2 and phospho-EGFR, Western blot analysis was performed. 5-Bromo-2′-deoxy-uridine (BrdU) and crystal violet staining were used to assess cell proliferation and cell viability, respectively. Results: The primary human tendon cells in culture expressed enzymes related to ACh synthesis (choline acetyltransferase and vesicular acetylcholine transporter), along with vimentin and tenomodulin, which confirm the tenocyte phenotype. The cells also expressed the M2 R. By administering exogenous ACh, the tenocytes were stimulated to significantly proliferate and increase in viability. In addition, Western blot showed that ACh stimulation resulted in increased phosphorylation of both EGFR and ERK1/2. When the cells were exposed to atropine, or the EGFR-blocking substance, the proliferative effect of ACh decreased. Simultaneously, the increase in ERK1/2 phosphorylation induced by incubation with ACh was effectively blocked in the presence of the mAChR antagonist atropine. Inhibition of either EGFR or MMP with specific blockers reduced the phosphorylation of ERK1/2. Discussion: Based on the results of the present study, as well as from previously established studies, we propose that human tenocytes, with their innate ability to produce ACh, increase ACh production during tendinosis development. Via an autocrine loop, the ACh produced by tenocytes stimulates mAChRs on the cell surface, thereby activating MMPs to cleave a cell surface-associated EGFR ligand. The ligand then binds to EGFR which in turn after activation increases ERK1/2 phosphorylation, leading to the increased cell proliferation and hypercellularity as seen in tendinosis (figure 1 ). In an early stage of tendinosis, hypercellularity might be a part of a healing or adaptive response, but in the chronic stage excessive tenocyte proliferation could be detrimental to tendon structure and function. The non-neuronal cholinergic system of tendon tissue is thus a possible target for future modulation of these processes in tendinosis.